2020
DOI: 10.3390/jcm9103330
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effect of Masticatory Muscle Activity with Transcutaneous Electrical Nerve Stimulation in Muscle Pain of Temporomandibular Disorders Patients

Abstract: Transcutaneous electrical nerve stimulation (TENS) is a non-invasive treatment modality for acute and chronic pain. However, little information for muscle activity is available on the immediate effects of TENS in masticatory muscle pain related to temporomandibular disorders (TMDs). The present study aimed to evaluate the immediate effects of TENS treatment on TMD-related muscle pain. Thirty-six patients with TMD-related muscle pain and 39 healthy subjects served as TMD and control groups, respectively. For ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Further, evidence suggests that CPM response in the trigeminal-innervated body regions is weaker compared with those in the extra-trigeminal innervated areas [ 62 ]. Third, transcutaneous electric nerve stimulation (TENS) has been suggested to manage TMD pain on the mechanisms of the resulting pain relief through the CNS mechanisms [ [63] , [64] , [65] ]. The basis for inhibitory effects of TENS on TMD pain is not fully understood, but the modulatory roles of TENS on descending pain controls in the CNS are considered [ 21 , 66 ].…”
Section: Neural Mechanisms For Pain In the Deep Craniofacial Tissues In Humanmentioning
confidence: 99%
“…Further, evidence suggests that CPM response in the trigeminal-innervated body regions is weaker compared with those in the extra-trigeminal innervated areas [ 62 ]. Third, transcutaneous electric nerve stimulation (TENS) has been suggested to manage TMD pain on the mechanisms of the resulting pain relief through the CNS mechanisms [ [63] , [64] , [65] ]. The basis for inhibitory effects of TENS on TMD pain is not fully understood, but the modulatory roles of TENS on descending pain controls in the CNS are considered [ 21 , 66 ].…”
Section: Neural Mechanisms For Pain In the Deep Craniofacial Tissues In Humanmentioning
confidence: 99%
“…A systematic review on TENS in the management of a different spectrum of TMDs found a significant and considerable (19.2-77%) reduction in painful sensations immediately after the treatment [20]. TENS not only relieved pain and improved masticatory functions [21] but also simultaneously decreased myoelectric activity of elevator muscles at rest [8]. Although TENS has been proved to be effective in different TMDs, few researchers have reported contrast findings in myofascial pain dysfunction [22] and bruxism [23].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional TENS was effective in improving the functional mouth opening, but the side effects such as tingling sensation and paresthesia occurred in some patients following TENS [ 20 ]. There was also significant increase in maximum mouth opening and the maximum bite force after conventional TENS in patients with TMD-related muscle pain, but one patient expressed negative feelings after TENS [ 21 ]. Previous evidence has also reported that conventional TENS reduced both pain and EMG activity of the anterior portion of the temporal muscle, increasing the activity of masseter muscles during maximum voluntary clenching in TMD patients.…”
Section: Discussionmentioning
confidence: 99%